PENGARUH EFEKTIVITAS PENGGUNAAN DAN KEPERCAYAAN TEKNOLOGI SISTEM INFORMASI TERHADAP KINERJA INDIVIDUAL - ARIYANTO, DODIK (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 1 (2008))
The implementation of information system technology in a company should consider user capability to be useful in supporting duty completion, and thus improve individual performance. Another important factor is user’s trust in reliability of the technology. This research is aims to investigate whether effectiveness of the use of and trust in information system technology affect individual performance. After passing the test of validity, reliability, and classical assumption, data are analyzed using ordinary least square method. The result demonstrates that effectiveness of the use of and trust in information system technology affect individual performance positively and significantly. Effectiveness variable affects individual performance of 47.7 percent, while trust variable influences is 77.1 percent. The second hypothesis is supported by respondents reply that in average they trust the technology of 80.9 percent. Therefore, it is concluded that effectiveness of the use of and trust in information system technology affect individual performance positively and significantly.
Keywords: information system technology, effectiveness of use of information system technology, trust in information system technology, individual performance